Illness Patterns, Utilisation of Health Services and the Use of Health Supplements among the Foreign Workers in Selected Areas of Peninsular Malaysia - Ab Sallam, Atiya (Faculty of Medicine, University of Malaya, 2002)
This paper examines the result of a section on recent illness of the health survey among 799 foreign workers from three selected study locations. The main objective was to study illness or injury patterns and the utilisation of available health care services. It also attempts to examine the use of health supplements as an indicator of self-care. Findings indicate that the illness or injury rate was 46.6%. The illness or injury rate increased with age and was highest in the 45-54 age group (65.0%) and among the Thai workers (69.6%). The main illnesses reported were injuries and accidents (19.6%), musculoskeletal problems (18.0%) and gastrointestinal complaints (16.7%), and it varied with gender, age and nationality. Almost 90% of the foreign workers sought treatment at modern health care facilities, with a third utilising government health care services. The employers contributed towards 60% of all the treatment costs. Nearly a third of the foreign workers took health supplements, and the rates were higher among the younger age group (40.0%) and among the Indonesian workers (52.0%). Majority had obtained the health supplements from the pharmacies or retail shops (43.3%) and private health care facilities (35.4%), and about 70% paid out of their own pocket. Some of the implications and limitations of these findings are discussed.